PENGARUH LOKUS KENDALI TERHADAP PERILAKU PENGELOLAAN KEUANGAN DENGAN PENGETAHUAN KEUANGAN SEBAGAI VARIABEL MODERATOR - Deya Amanda, Regita; Puspita Adiati, Rosatyani (Lafadz Jaya Publisher, 2023)
Financial problems, one of which is carelessness in managing finances, cause Generation Y's finances to become irregular. Rampant buying of branded clothes, hanging out in cafes, and going on holiday impulsively, accompanied by a lack of financial knowledge, means they don't have good control over their income, so they don't have savings, investments, insurance, or long-term financial plans. This research was conducted to examine the influence of locus of control on financial management behavior in Generation Y in Indonesia, with financial knowledge as a moderator variable. The quantitative survey method was used to collect 122 research samples aged 23–43 years from various cities in Indonesia. The measuring instruments used are the IPC-Scale, the FMBS (Financial Management Behavior Scale), and the Financial Knowledge Scale. Research data analysis was carried out using simple linear regression analysis and moderated regression analysis. The results of this research show that there is a significant influence of locus of control on the financial management behavior of Generation Y in Indonesia, and financial knowledge can't moderate the influence of this relationship model.